2017
DOI: 10.1177/0018720817747730
|View full text |Cite
|
Sign up to set email alerts
|

Why Do I Have to Drive Now? Post Hoc Explanations of Takeover Requests

Abstract: 13Objective: It was investigated whether providing an explanation for a take-over request in automated 14 driving influences trust in automation and acceptance. 15 Background: Take-over requests will be recurring events in conditionally automated driving which 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 87 publications
(104 reference statements)
8
47
2
Order By: Relevance
“…We also found RtI frequency to lower usability, which was not expected but can probably be explained by the activation process of the implemented automation. As hypothesized (based on Körber et al [39]), RtI frequency showed no effect on trust. Furthermore, subjective time use was decreased by more RtIs.…”
Section: Transition Frequencysupporting
confidence: 51%
See 1 more Smart Citation
“…We also found RtI frequency to lower usability, which was not expected but can probably be explained by the activation process of the implemented automation. As hypothesized (based on Körber et al [39]), RtI frequency showed no effect on trust. Furthermore, subjective time use was decreased by more RtIs.…”
Section: Transition Frequencysupporting
confidence: 51%
“…Based on findings on the effects of interruptions and the connection between acceptance and perceived usefulness, we hypothesize that with more RtIs workload is elevated and acceptance reduced. An impact on trust and usability is not expected, based on findings by Körber et al [39]. The predictive HMI is expected to have a positive effect on usability, workload, trust, and acceptance, like it was found in studies outlined above.…”
mentioning
confidence: 86%
“…functions and monitor roadway conditions for an entire trip" (National Highway Traffic Safety Administration [NHTSA], 2013, p. 5). However, the AV automation level of the prior literature simulated level 2 and level 3 automation(Forster et al, 2017;Koo et al, 2015Koo et al, , 2016Körber et Du, N., Haspiel, J., Zhang, Q., Tilbury, D., Pradhan, A., Yang, X. J. and Robert, L. P. (Accepted May 21, 2019). Look Who's Talking Now: Implications of AV's Explanations on Driver's Trust, AV Preference, Anxiety and Mental Workload, Transportation Research Part C: Emerging Technologies, forthcoming.…”
mentioning
confidence: 99%
“…Study results showed that the inclusion of system uncertainty information positively enhanced the interaction in terms of trust and acceptance. Körber et al [32] evaluated whether providing an additional explanation for a takeover request in automated driving influenced trust in automation and acceptance. Results revealed that an additional explanation for a takeover request did not influence trust or acceptance but increased the perceived understanding of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The IC (3) was divided into three parts and displayed the current mode of the automated system, a bird's view of the current traffic situation, relevant navigational information, and planned system maneuvers. Additionally, the reason the automation stopped (e.g., construction site, end of motorway) was depicted to positively enhance participants' system understanding [32]. AR 4elements were used to highlight the surrounding relevant vehicles in takeover scenarios.…”
mentioning
confidence: 99%